Sterilization of Thiol‐ene/Acrylate Based Shape Memory Polymers for Biomedical Applications. Issue 2 (12th October 2016) - Ecker, Melanie; Danda, Vindhya; Shoffstall, Andrew J.; Mahmood, Samsuddin F.; Joshi‐Imre, Alexandra; Frewin, Christopher L.; Ware, Taylor H.; Capadona, Jeffrey R.; Pancrazio, Joseph J.; Voit, Walter E.
Abstract : Sterilization of shape memory polymers for biomedical devices with self‐softening capabilities is demonstrated. Ethylene oxide is shown to be an appropriate method to sterilize temperature sensitive thiol‐ene/acrylate polymers. The thermomechanical properties and softening characteristics of the shape memory polymers are not affected as demonstrated by dynamic mechanical analysis on dry and in phosphate buffered saline immersed samples. Abstract : A fundamental study on the sterilization of thiol‐ene/acrylate polymers for biomedical applications is presented. These polymer networks belong to the emerging field of shape memory polymers and have the capability to undergo softening after insertion into the body. The impact of various sterilization methods, such as radiation, steam, and ethylene oxide on the thermomechanical properties of these stimuli responsive materials is investigated. Time and temperature dependent thermomechanical properties of sterilized and nonsterilized samples are determined by means of dynamic mechanical analysis in an aqueous environment to allow testing of polymers in phosphate buffered saline. The findings show that ethylene oxide sterilization is appropriate for thiol‐ene and thiol‐ene/acrylate based shape memory polymers. This method does not adversely affect thermomechanical and self‐softening properties and after sterilization, endotoxin levels remain below the thresholds recommended in the FDA Guidance.